Connecting primary and specialized metabolism: Amino acid conjugation of phytohormones by GRETCHEN HAGEN 3 (GH3)acyl acid amido synthetases - Jez, J. M.
GRETCHEN HAGEN 3 (GH3)acyl acid amido synthetases catalyze the ATP-dependent conjugation of phytohormones with amino acids. Traditionally, GH3 proteins are associated with synthesis of the bioactive jasmonate hormone (+)-7- iso -jasmonoyl-L-isoleucine (JA-Ile)and conjugation of indole-3- acetic acid (IAA)with amino acids that tag the hormone for degradation and/or storage. Modifications of JA and IAA by GH3 acyl acid amido synthetases help maintain phytohormones homeostasis. Recent studies broaden the roles of GH3 proteins to include the regulation of JA biosynthesis; the modification of other auxins (i.e., phenylacetic acid and indole- 3-butyric acid); the conjugation of auxinic herbicides, such as 4-dichlorophenoxyacetic acid, 4-(2,4-dichlorophenoxy)butyric acid, and dicamba; and the missing step in the isochorismate pathway for the biosynthesis of salicylic acid. The GH3 protein family joins the growing number of versatile enzyme families that blur the line between primary and specialized metabolism for an increasing range of biology functions.
Keywords: ACYL ACID AMINO SYNTHETASE; AUXIN; GRETCHEN HAGEN 3 PROTEIN; JASMONIC ACID; PHYTOHORMONE; PROTEIN STRUCTURE; SALICYLIC ACID